Performance and carcass characteristics of yearling bulls on winter pastures subjected to grazing intensities - da Rocha, Lemar Maciel; Carvalho, Paulo César de Faccio; Baggio, Carolina; Anghinoni, Ibanor; Terra Lopes, Marília Lazzarotto; Macari, Stefani; da Silva, Jamir Luis Silva (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to assess the grazing intensity effects on the finishing of yearling bulls, in winter pastures in succession to soybean crop. Sward pre-grazing different heights of mixed pasture between ryegrass and oat were evaluated: 10, 20, 30 and 40 cm. A randomized complete block design was utilized with three replicates. Ten-month-old beef crossbred bulls were used, with initial live weight of 192±12 kg. The following variables were evaluated: forage mass and allowance, sward height, forage daily accumulation rate and forage total accumulation, average daily weight gain (ADG), stocking rate and weight gain per unit area (GA), as well as the qualitative characteristics of the carcasses. The yearling bulls were slaughtered at 14 months of age. ADG fitted a quadratic model, with maximum performance between 20 and 25‑cm sward height, while GA fitted a negative linear model. Yearling bulls showed a satisfactory carcass quality when pastures were managed with pre‑grazing heights higher than 10 cm. It is possible to finish yearling bulls in the pasture phase of integrated production systems, during winter, in succession to soybean crop. The management of ryegrass and oat mixed pastures at sward pre-grazing heights of 20 and 25 cm optimize individual animal performance and per area unit.